Grandparents : a special kind of love - LeShan, Eda J.; Taggart, Tricia (New York : Macmillan, 1984)
1. Grandparents--Juvenile literature 2. Conflict of generation
Faculty
Keywords: Grandparents -- Juvenile literature; Interpersonal relations -- Juvenile literature; Love -- Juvenile literature; Conflict of generations -- Juvenile literature; Grandparents; Conflict of generations